A meta-analysis of the criterion-related validity of Session-RPE scales in adolescent athletes - Haochong Liu; Wenpu Yang; Haoyang Liu; Dapeng Bao; Yixiong Cui; Indy Man Kit Ho; Qian Li (BMC, 2023)
Abstract Background The objective of this study was to establish the criterion-related validity of the session-rating of perceived exertion (s-RPE) method in adolescent athletes. Methods According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines, a meta-analysis (PROSPERO ID: CRD42022373126) was performed using Stata 15.1 software. Eight databases using the following terms: ('s-RPE' OR 'Rating Perceived Exertion session' OR 'RPE session' OR 'RPE' OR 'Rate of Perceived Exertion' OR 'Rated of Perceived Exertion') AND ('Adolescen*' OR 'Youth*' OR 'Teen*') AND ('validity' OR 'correlation' OR 'concurrent validity') were searched up to 2022. Articles meeting the inclusion criteria were screened and adopted the "Methodological Index for Non-Randomized Studies (MINORS)" to evaluate the risk of bias. Results An initial 1798 studies using the s-RPE method were identified and finally, a total of 16 studies were included for further analysis. The relationship between assessment instruments CR-10 or CR-100 modified methods of s-RPE and the heart rate measures of these selected studies were calculated using correlation coefficient (r values) and Fisher's z-score. A strong to very strong correlation between s-RPE and HR was observed (overall: r = 0.74; CR-10: r = 0.69; CR-100: r = 0.80). CR-100 scale (Fisher's z = 1.09) was shown to have a higher criterion validity than that of the CR-10 scale (Fisher's z = 0.85). Conclusion Preliminary findings showed that s-RPE using either CR-10 or CR-100 scales can be used "stand-alone" for monitoring internal training load for children and adolescent athletes. Future studies should focus on whether CR-100 could better perform than CR-10 for junior and children athletes in different age groups and sports as well as the causes leading to potential scoring biases.